Answer :
Answer:
x = 2, Inverse property of subtraction
Step-by-step explanation:
Simplifying
2(x + 3) = 10
Reorder the terms:
2(3 + x) = 10
(3 * 2 + x * 2) = 10
(6 + 2x) = 10
Solving
6 + 2x = 10
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + 2x = 10 + -6
Combine like terms: 6 + -6 = 0
0 + 2x = 10 + -6
2x = 10 + -6
Combine like terms: 10 + -6 = 4
2x = 4
Divide each side by '2'.
x = 2
Simplifying
x = 2
Answer:
x = 2
Step-by-step explanation:
- Apply the distributed property, so it now looks like this: 2x + 6 = 10
- Subtract 6 to each side, so it now looks like this: 2x = 4
- Divide each side by 2 to cancel out the 2 next to x. It should now look like this: x = 2
I hope this helps!